Numerical analysis of vortex and cavitation dynamics of an axial-flow pump - Jie Gong; Wan-zhen Luo; Tie-cheng Wu; Zhi-yuan Zhang (Engineering Applications of Computational Fluid Mechanics, 2022)
This study focuses on the correlative mechanism of the ambient pressure and inflow uniformity on the vortex and cavitation dynamics of an axial flow pump. The shear stress transport k – ω turbulence model and Schnerr–Sauer cavitation model are applied in the unsteady detached eddy simulation. The results show that the vortex merging between the primary and secondary tip leakage vortices (TLV) happens earlier with the growth of the cavity at a lower ambient pressure. The contact position of the merged TLV to the adjacent blade moves upstream with the decrease in the cavitation number. As the uniformity of the axial inflow decreases, TLV merging and vortex shedding are also promoted. The nonlinear variation of the initial angle of attack of the impeller blade leads to the compression or expansion of sheet cavitation under non-uniform inflow conditions. The evolution process and energy transfer of the vortices are verified quantitatively using a power spectral density analysis of kinetic energy fluctuations, and the short-wave instability leads to the fast decline of spectrum peaks at a higher frequency in the cavitating flow. It is crucial to avoid severe changes of ambient pressure and inflow uniformity to ensure the design performance of pump in actual working environment.